2009
DOI: 10.1111/j.1365-2648.2008.04905.x
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain: prevalence and associated risk factors among hospital staff

Abstract: Preventive measures should be taken to reduce the risk of lower back pain, such as arranging proper rest periods, educational programmes to teach the proper use of body mechanics and smoking cessation programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
221
9
26

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(290 citation statements)
references
References 42 publications
23
221
9
26
Order By: Relevance
“…Similar to previous studies, lower back pain (LBP) was the most prevalent site where almost half of the students complained of lower back pain in the past week [5].…”
Section: Discussion:-supporting
confidence: 70%
“…Similar to previous studies, lower back pain (LBP) was the most prevalent site where almost half of the students complained of lower back pain in the past week [5].…”
Section: Discussion:-supporting
confidence: 70%
“…Among these are assuming particular postures 8 (O'Sullivan et al 2002), though this aspect is not considered a risk for the bone, muscular and articular apparatus by the Legislative Decree 81/08 (Decreto legislativo 81/08), but when these postures are incorrect (Colombini et al 1995) they may induce a sense of discomfort, fatigue and pain in a matter of a short term. A greater degeneration of the entire lumbar rachis, and particularly of the lower lumbar region, is also correlated to the handling of loads with frequent lifting, pushing and tractions, especially in absence of mechanical devices (Karahan et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Various studies report association between musculoskeletal disorders, occupational injury, impairment, disability (Klein et al 1984;Daraiseh et al 2003;Sherehiy et al 2004;Karwowski et al 2005;Karahan et al 2009) and work-related risk factors for musculoskeletal complaints in the nursing profession. Among work-related risk factors, the physical events like lifting, awkward postures and stooping (Engels et al 1996;Schenk et al 2007), are considered the most important sources of this kind of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified job factors that may contribute to WMDs among healthcare workers [2,3]. The job factors and activities indicated by healthcare workers as being related to the appearance or exacerbation of WMDs include handling and transporting patients [4,5,6,7]. There are few studies in the literature on WMDs among physical therapists.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that many health and safety professionals assume that the physical therapists' knowledge base of body mechanics, rehabilitation, and injury prevention may be a protective factor for the development of WMDs [8]. However, a recent study involving all healthcare workers from six hospitals demonstrated that nurses and physical therapists were the healthcare professionals most affected by WMDs [4].…”
Section: Introductionmentioning
confidence: 99%